Implementation of e-marketing via instragram on the sustainability of MSMEs in the face of the covid-19 pandemic in Baubau city - Silviani.A, Wa Ode Rhevi (COMMICAST, 2022)
The Covid-19 pandemic has had such a big impact on all circles, especially students who are overseas.Since the implementation of government policies, namely lockdown and social distance in various regions, many overseas students have turned to become MSME activities for their survival.Not only that.The impact of the Covid-19 pandemic has also weakened several sectors, especially the economic sector.In the midst of this pandemic, many MS activities have difficulty developing their businesses.In this study, this study saw the extent of students implementing E-Marketing MSMEs via Instagram in the city of BAUBAU Covid-19 pandemic .This study uses a qualityative method with a phenomenal approach.This research proves that the implementation of e-marketing linguistics through Instagram carried out by MS developers is in accordance with consumers marketing. I implemented especially in the midst of the Covid-19 Pedemic so business activities continue and generate economic value.Keywords:E-Marketing, Instagram, UMKM, and Covid-19